MRVI1 and NTRK3 Are Potential Tumor Suppressor Genes Commonly Inactivated by DNA Methylation in Cervical Cancer - Ji, Huihui; Li, Kehan; Jiang, Wenxiao; Li, Jingwei; Zhang, Jian-an; Zhu, Xueqiong (Frontiers in Oncology, 2022)
The abnormally methylated tumor suppressor genes (TSGs) associated with cervical cancer are unclear. DNA methylation data, RNA-seq expression profiles, and overall survival data were downloaded from TCGA CESC database. DMGs and DEGs were obtained through CHAMP and DESeq packages, respectively. TSGs were downloaded from TSGene 2.0. Candidate hypermethylated/down-regulated TSGs were further evaluated and pyrosequencing was used to confirm their difference in methylation levels of selected TSGs in cervical cancer patients. A total of 25946 differentially methylated CpGs corresponding to 2686 hypermethylated genes and 4898 hypomethylated genes between cervical cancer and adjacent normal cervical tissues were found in this study. Besides, 693 DEGs (109 up-regulated and 584 down-regulated) were discovered in cervical cancer tissues. Then, 192 hypermethylated/down-regulated genes were obtained in cervical cancer compared to adjacent tissues. Interestingly, 26 TSGs were found in hypermethylated/down-regulated genes. Among these genes, low expression of MRVI1 and NTRK3 was associated with poor overall survival in cervical cancer. Moreover, GEO data showed that MRVI1 and NTRK3 were significantly decreased in cervical cancer tissues. The expression levels of MRVI1 and NTRK3 were negatively correlated with the methylation levels of their promoter CpG sites. Additionally, elevated methylation levels of MRVI1 and NTRK3 promoter were further verified in cervical cancer tissues by pyrosequencing experiments. Finally, the ROC results showed that the promoter methylation levels of MRVI1 and NTRK3 had the ability to discriminate cervical cancer from healthy samples. The study contributes to our understanding of the roles of MRVI1 and NTRK3 in cervical cancer.